Maximize utilization of public bus transport service - Manimaran, Hemavathi; Zainuddin, Nizamuddin (2012)
The increasing number of private vehicles and the ailing public bus transport (PBT) service industry is a testimony that the Malaysian citizens prefer driving to utilizing PBT. The overall improvement to the PBT is vital to encourage the modal switching and increase the utilization rate to meet the 6th Bidang Keberhasilan Utama Negara (NKRA) (the star, 2009). The increased in the number of private vehicles on the road in Malaysia testifies to the preference of driving to work or places of leisure for many reasons. The overall improvement of public transportation augmented with selective restrictions of private vehicle use would invariably improve the utilization of public transportation. This research proposes a conceptual pattern to assess perceived Bus transport utilization. It uses a secondary data to identify the preferences of Bus commuters to assess utilization. The results showed that the most significant service driver influencing the overall perceived utilization is season ticket, followed by information service, ticket pricing, and reliability of schedule, safety and comfort. Reliability of schedule, safety and comfort however were not significant on the perceived direct utilization.The findings attempt to assist the PBT authorities in strategic planning to increase the utilization and to sustain the PBT service industry which could lead to economic growth and improved quality of life.